Feminist pedagogies in a time of backlash. Issue 2 (17th February 2021) - Elwell, Alice; Buchanan, Rachel
ABSTRACT: Gender equity in Australian schooling is no longer the policy focus that it once was. Within the contemporary secondary schooling system, teachers can find it challenging to enact feminist pedagogies. Using a narrative approach, we explore the experiences of two secondary teachers in Queensland. These teachers articulate the realities of using feminist pedagogies in a time dominated by reactionary politics and market-based schooling. Their stories suggest that their use of feminist pedagogies: is shaped by their feminist identities; has made them attuned to the gender politics of their school context; and can generate safe classroom spaces. The struggles and successes that they describe, as well as the confrontations and uncertainties that they face, reveal that while not easy, it is possible to utilise feminist pedagogies in a time of backlash.